Perancangan Value Proposition Canvas untuk Produk Layanan Digitalisasi UMKM PT XYZ - Muhammad Haris Suwandi; Farda Hasun; Muhammad Almaududi Pulungan (MES Bogor, 2024)
The digitalization services for MSMEs (Micro, Small, and Medium Enterprises) by PT. XYZ are designed to provide consistent and high-quality internet connectivity to support various MSME businesses in Indonesia. This service aims to assist MSME operations digitally, reducing operational costs and increasing productivity in the era of globalization. However, in the last year, PT. XYZ has failed to meet its sales targets. The main cause of this issue is that PT. XYZ has not been able to offer services that align with the customer profile. To address this, the research focuses on designing a Value Proposition Canvas for PT. XYZ’s digitalization services for MSMEs. The study begins by gathering data on the current services, competitor products, and PT. XYZ’s strategies through literature review and company documentation. Additionally, data on customer profiles are collected through observations and interviews with 10 MSMEs, which are then mapped into customer profiles consisting of customer jobs, pains, and gains. This data is used to design a value map. Subsequently, a strategy canvas is developed, comparing the analyzed products with several competitors. Based on this strategy canvas, an improvement process is carried out using the ERRC grid to develop a new value proposition canvas. Some proposed improvements from this research include an all-in-one MSME digitalization package and a bundled digital marketing system package.